Intervensi Psikoedukasi Pola Asuh Orangtua dalam Mengoptimalkan Perkembangan Sosial-Emosional Anak Usia Dini - Rizka Fibria Nugrahani; Hilda Rosa Ainiyah; Laila Indra Lestari (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Parental parenting plays a crucial role in shaping early childhood development, including cognitive, social, and emotional aspects. However, the level of public understanding of effective parenting in Indonesia remains relatively low, potentially hindering optimal child development. This study highlights various parenting styles, including democratic, permissive, and authoritarian parenting, as well as the impact of inappropriate parenting on children's development. Findings indicate that unsupportive parenting styles, such as authoritarian or permissive parenting, can lead to social difficulties, low independence, and disruptions in emotional and cognitive development. Therefore, educational efforts for parents are essential to help them adopt more effective parenting strategies that support optimal early childhood development.